Assessing the Effect of Hospital Accreditation on Patient Safety Culture in Healthcare Facilities in Saudi Arabia: A Comprehensive Review - Mohanad Hamad Aljehimi; Talal Hamza Alrashidi; Theeb Dashin Alqatani; Salamah Jali Alotaibi; Saad Mohammed Al Samra; Waleed mansour saeed Alqahtani; Mohammed saeed Alqahtani; Fayez Mathkar Humud Aladhyani; Mohammed Hamed Alanazi; Motlag Abdullah L Alaotibi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
This comprehensive review examines the impact of hospital accreditation on patient safety culture in healthcare facilities in Saudi Arabia, with a focus on the Central Board for Accreditation of Healthcare Institutions (CBAHI) standards. Patient safety culture, defined as shared values and practices prioritizing safety, is critical for reducing medical errors and improving healthcare outcomes. The study highlights Saudi Arabia’s progress in healthcare quality through accreditation, while identifying challenges in fostering a consistent safety culture across diverse healthcare settings. Empirical evidence from recent studies, including a cross-sectional assessment of 340 healthcare workers in Saudi public hospitals, reveals that accreditation significantly enhances technical safety measures, such as facility management and emergency preparedness. However, leadership commitment and organizational culture remain underdeveloped, indicating a gap between structural compliance and cultural transformation. Demographic factors, including profession, education level, and nationality, influence perceptions of safety culture, with physicians and experienced staff generally viewing accreditation more favorably. The review underscores the strengths of accreditation, such as standardized safety practices and external validation, while addressing limitations like inconsistent leadership engagement and sustainability concerns. Recommendations for improvement include national prioritization of patient safety, enhanced training programs, non-punitive reporting systems, and dedicated safety officers. By bridging these gaps, Saudi healthcare facilities can achieve a robust safety culture aligned with international standards, ultimately improving patient care and outcomes.